Implementasi Supervisi Pendidikan Kepala Sekolah sebagai Wahana Evaluasi Kinerja Tenaga Pendidik dan Kependidikan - Felisa Dwi Mubarika; Hanna Nurul Imani; Kahfisah Astrella; Muhammad Febry; Novia Putri Arianti (Proceedings Series of Educational Studies, 2023)
Abstract: Education is something that will never get bored if it is discussed and we examine it and become the subject of discussion. Starting from the curriculum, teaching staff, educational staff, scientific innovation, to educational supervision that supports learning programs in educational institutions and how to evaluate educational programs, especially in elementary schools. The principal as a supervisor has the burden of the role and responsibility of monitoring, fostering and improving the teaching and learning process in the classroom or at school. This responsibility is known as the responsibility of supervision. This article was compiled with the aim of exploring and analyzing the basic concepts and roles of supervision in evaluating educational programs. the focus is on elementary schools in the city of Malang. By differentiating how the evaluation of educational programs in each school, we are sure to get a significant difference. The research in this article uses qualitative research. Group members go directly to the field to conduct interview observations and collect data and report it. The research was carried out together with several educators at different educational institutions. In research group members found many advantages of educational supervision in supporting the learning process, so here the role of supervision is very important. Increasing the competence of educators with educational supervision is expected to be even better.Keywords: principal; educational supervision; educators; evaluation of education programs; educational programAbstrak: Pendidikan adalah sebuah hal yang tidak akan pernah bosan jika dibahas dan kita teliti dan menjadi pembicaraan. Mulai dari kurikulum, tenaga pendidik, tenaga kependidikan, inovasi ilmu pengetahuan, sampai dengan supervisi pendidikan yang menunjang program pembelajaran di lembaga pendidikan serta bagaimana evaluasi dari program pendidikan khususnya di Sekolah Dasar. Kepala sekolah sebagai supervisor memiliki beban peran dan tanggungjawab memantau, membina, dan memperbaiki proses belajar mengajar di kelas atau di sekolah. Tanggungjawab ini dikenal sebagai tanggungjawab supervisi. Artikel ini disusun bertujuan untuk mengulik dan menganalisis bagaimana konsep dasar serta peran supervisi dalam evaluasi program pendidikan. fokusnya adalah sekolah dasar yang ada di Kota Malang. Dengan membedakan bagaimana evaluasi program pendidikan di masing-masing sekolah, kami yakin akan mendapatkan sebuah perbedaan yang substansial. Penelitian dalam artikel ini menggunakan penelitian kualitatif. Anggota kelompok memilih untuk turung langsung kedalam lapangan yang ada untuk melakukan kegiatan observasi, wawancara, mengumpulkan data, lalu melaporkannya. Penelitian dilaksanakan bersama dengan beberapa tenaga pendidik di lembaga pendidikan yang berbeda. Dalam penelitian anggota kelompok menemukan banyak keunggulan supervisi pendidikan dalam menunjang proses pembelajaran, jadi disini peran supervisi sangat penting. Peningkatan kompetensi tenaga pendidik dengan adanya supervisi pendidikan diharapkan dapat menjadi lebih baik lagi.Kata kunci: kepala sekolah; supervisi pendidikan; tenaga pedidik; evaluasi program pendidikan; program pendidikan